Cohort profile: pathways to care among people with disorders of sex development (DSD). Issue 9 (21st September 2022) - Goodman, Michael; Yacoub, Rami; Getahun, Darios; McCracken, Courtney E; Vupputuri, Suma; Lash, Timothy L; Roblin, Douglas; Contreras, Richard; Cromwell, Lee; Gardner, Melissa D; Hoffman, Trenton; Hu, Haihong; et al.
Abstract : Purpose: The 'DSD Pathways' study was initiated to assess health status and patterns of care among people enrolled in large integrated healthcare systems and diagnosed with conditions comprising the broad category of disorders (differences) of sex development (DSD). The objectives of this communication are to describe methods of cohort ascertainment for two specific DSD conditions—classic congenital adrenal hyperplasia with 46, XX karyotype (46, XX CAH) and complete androgen insensitivity syndrome (CAIS). Participants: Using electronic health records we developed an algorithm that combined diagnostic codes, clinical notes, laboratory data and pharmacy records to assign each cohort candidate a 'strength-of-evidence' score supporting the diagnosis of interest. A sample of cohort candidates underwent a review of the full medical record to determine the score cutoffs for final cohort validation. Findings to date: Among 5404 classic 46, XX CAH cohort candidates the strength-of-evidence scores ranged between 0 and 10. Based on sample validation, the eligibility cut-off for full review was set at the strength-of-evidence score of ≥7 among children under the age of 8 years and ≥8 among older cohort candidates. The final validation of all cohort candidates who met the cut-off criteria identified 115 persons with classic 46, XX CAH. The strength-of-evidence scores among 648 CAIS cohort candidates ranged from 2 to 10. There were no confirmed CAIS cases among cohort candidates with scores <6. The in-depth medical record review for candidates with scores ≥6 identified 61 confirmed cases of CAIS. Future plans: As the first cohort of this type, the DSD Pathways study is well-positioned to fill existing knowledge gaps related to management and outcomes in this heterogeneous population. Analyses will examine diagnostic and referral patterns, adherence to care recommendations and physical and mental health morbidities examined through comparisons of DSD and reference populations and analyses of health status across DSD categories.